SNR-Based Antenna Selection with Threshold Value in Wireless Channels - Aydin, Erdogan; Ilhan, Haci; Ozdemir, Ozgur (IEEE, 2013)
In this study, in order to reduce the end-to-end bit error rate (BER) at the destination, two different antenna selection models based on signal to noise ratio (SNR) have been proposed. Relay node contains multiple antennas and BPSK modulation is used. In these models under consideration, different optimal decision rule is determined theoretically. To generate each threshold decision rule, either instantaneous and average SNR or both together in S -> D, S -> R and R -> D links are used. Proposed antenna selection algorithm with the optimal threshold value can reduce significantly the end-to-end BER according to the simple relaying technique.
Keywords: Cooperative diversity; antenna selection; SNR based selection relaying; PERFORMANCE; DIVERSITY; BOUNDS; Engineering; Telecommunications